Echocardiographic assessment in patients with chronic kidney disease: Current update. Issue 4 (7th March 2017) - Sulemane, Samir; Panoulas, Vasileios F.; Nihoyannopoulos, Petros
Abstract : Patients with chronic kidney disease (CKD) carry a high cardiovascular risk. An abundance of evidence has emerged in recent years establishing minor reductions in estimated glomerular filtration rate as an independent risk factor for cardiovascular mortality. Additionally, cardiac changes, such as left ventricular hypertrophy and impaired left ventricular systolic function, have been associated with an unfavorable prognosis. Despite the significant prevalence of underlying cardiac abnormalities, symptoms may not manifest in many patients with CKD. A range of available and emerging echocardiographic modalities may assist with diagnosing heart disease in CKD. Furthermore, some of these emerging techniques can give an important insight into the pathophysiology of subclinical dysfunction in CKD. This review discusses how current and emerging echocardiographic modalities such as speckle tracking echocardiography and 3D echocardiography might help cardiologists in providing important information to help with diagnosis and risk stratification of cardiac‐related morbidity and mortality in patients with renal disease, as well applicability of these tools to current clinical practice.